Large-Scale Post-Glacial Distribution of Vegetation Structures in the Mediterranean Region (Recent Dynamics of the Mediterranean Vegetation and Landscape, 2005)
This chapter contains sections titled: * Introduction * The Large-Scale Vegetation Structures * Conclusions * Acknowledgements